The Effectiveness of the Vocabulary Notebook in Learning English Vocabulary by Libyan Master’s Students - Emhemed, Abdussalam Saleh Khalafallah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This study was designed to investigate the perceptions of master’s students about vocabulary learning in EFL, and the effectiveness of using vocabulary notebooks in vocabulary acquisition. A qualitative approach was followed to collect data from 11 participants who were all Libyan master’s students in Eastern Mediterranean University. The data was gathered through individual semi-structured interviews with the participants and subsequently analyzed qualitatively. The results show that participants assign different roles to vocabulary and keeping a vocabulary notebook was recognized as a useful language learning strategy, expressing positive attitudes towards using one. Participants also reported that the vocabulary notebook helped vocabulary learning and language skills in many respects. The results suggest that the vocabulary notebook is not just a simple strategy for recording vocabulary but a complex engagement that has an impact on different aspects of language learning. Vocabulary notebooks, therefore, should be given more attention especially in an EFL context. They should be part of language teaching to make the learning of the target language more efficient.

ÖZ: Bu çalışma yüksek lisans öğrencilerinin yabancı dil olarak İngilizce’de sözcük öğrenimi hakkındaki algılarını ve sözcük defteri kullanımının dil edinimindeki etkinliğini araştırmak amacıyla tasarlanmıştır. Veriler nitel araştırma yöntemi kullanılarak Doğu Akdeniz Üniversitesi’nde okuyan 11 Libyalı yüksek lisan öğrencisinden toplanmıştır. Veriler katılımcılarla bire-bir gerçekleştirilen yarı-yapılandırılmış mülakatlar yoluyla elde edilmiş ve akabinde nitel bir biçimde çözümlenmiştir. Çıkan sonuçlara göre, katılımcılar kelime haznesine çeşitli roller yüklemekte ve sözcük defteri kullanımını da olumlu tutumlarını dile getirerek yararylı bir dil öğrenme stratejisi olarak görmektedirler. Katılımcılar ayrıca sözcük defterinin kelime ve dil becerisi öğrenimine yardımcı olduğunu kaydetmişlerdir. Bu sonuçlar sözcük defterinin yalnızca basit bir kelime not etme stratejisi değil, dil öğreniminin farklı boyutlarına etki eden karmaşık bir uğraş olduğunu ortaya koymaktadır. Bundan dolayı sözcük defterine özellikle yabancı dil olarak İngilizce öğrenimi bağlamında daha fazla önem verilmelidir. Sözcük defteri öğrencilerin hedef dili daha etkin bir şekilde öğrenebilmeleri için dil sınıflarına entegre edilmelidir.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2016. Supervisor: Assist. Prof. Dr. İlkay Gilanlıoğlu.
Keywords: English Language--Study and Teaching--Eastern Mediterranean University--Cyprus, North; Vocabulary Learning; Vocabulary notebook; vocabulary learning strategies; vocabulary learning; vocabulary acquisition; English Language Teaching (ELT)